Critical thinking: a key competency in the twenty-first century to deal with uncertainty and complexity - Funke, Joachim (Critical thinking across cisciplines, Vol. 2, Applications in the digital age, 2025)
Today’s world is becoming more complex and uncertain than it has ever been. Therefore, solving complex problems has become one of the key competencies in the twenty-first century. But what does that mean? Complex problems have different features that require special competencies, such as: to reduce complexity, to live with intransparency, to handle conflicting goal situations, and to understand the dynamics of a system. Critical thinking proves to be a key factor when it comes to dealing with uncertainty and complexity. Problems are nowadays not merely about the finding of information, but also about the evaluation of found information. In addition, value systems are important decision-making aids concerning conflicting goals. An important target of educational institutions is to establish critical thinking as a major element of their curriculum.
Gesehen am 26.02.2026